Carbon Inputs and Water Uptake in Deep Soils of an Eastern Amazon Forest - Davidson, Eric; Lefebvre, Paul A; Brando, Paulo M; Ray, David M; Trumbore, Susan E; Solorzano, Luis A; Ferreira, Joice N; Bustamante, Mercedes M. da C; Nepstad, Daniel C (Forest science, 2011)
Rooting depth affects soil profiles of water uptake and carbon inputs. Here we explore the importance of deep roots in a mature tropical forest of eastern Amazonia, where a throughfall exclusion experiment was conducted to test the resilience of the forest to experimentally induced drought. We hypothesized that soil water depletion occurred below the depth previously measured by sensors in 11-m-deep soil pits and that only a small root biomass is necessary to affect water uptake and the isotopic signature of soil CO2. A noninvasive electrical profiling method demonstrated greater depletion of soil water in the 11-18 m depth increment in the exclusion plot compared with the control plot by the end of the 3rd year of the experiment. A fine root biomass of only 0.1 g/cm3 measured at 3-6 m was sufficient for soil water drawdown and for imparting an isotopic signature of modern soil 14CO2 in both plots. A soil 13CO2 profile indicated drought stress in the exclusion plot. Fine root inputs of organic C to deep soils are small with respect to the carbon dynamics of the forest, but the deep rooting habit clearly affects the ecosystem water balance and profiles of soil CO2.